Pengembangan Media Learning with Music untuk Meningkatkan Keterampilan Menulis Puisi pada Siswa Kelas X MAN 3 Langkat T.P 2022/2023 - Sulistiawati, Novi; Amaluddin, Amaluddin (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aims to explore the development, feasibility, and effectiveness of Learning With Music Media for Poetry Text Material in Class X High School. Following the ADDIE developer model, the study progresses through research, data collection, design, product development, implementation, and evaluation. The population consists of 318 students, with a sample of 33 students. The developed product received a "Decent" rating, with media experts I and II providing "Very Eligible" criteria of 90% and 89%, respectively. Material experts I and II rated it as "Decent" at 80% and 82%. Teacher assessment yielded a "Very Eligible" rating of 96%. Field implementation with 33 students from class X IPA 3 at MAN 3 Langkat achieved a "Very Eligible" rating of 90%. The effectiveness test, conducted through evaluation sheets, revealed a "Very Effective" criterion of 90.15%.